2016
DOI: 10.1002/ghg.1621
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and regeneration studies of CO2 adsorption on activated carbon

Abstract: The kinetic and thermodynamic studies of CO2 adsorption on activated carbon were carried out in a fixed bed. Six different CO2 concentrations (from 5% up to 18 vol.%) and four temperatures (303 K, 313 K, 323 K, and 333 K) were applied to investigate dynamic adsorption behaviors. It showed that the increase in temperature led to faster adsorption kinetics, but also reduced the adsorption capacity. An isotherms modeling was made by the Langmuir isotherm model. The experimental isotherms data were well fitted. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Among the available methods, most research focus has been given to the post-combustion methods as they can be retrofitted more easily to the existing industrial units, compared to the Oxy-fuel and Pre-combustion methods [229]. Traditional post-combustion capture methods are absorption [18,19,[231][232][233][234][235][236], adsorption [13,18,[237][238][239], membrane gas separation [240][241][242][243][244][245][246], calcium looping [19,[247][248][249] and mineral carbonation [110,[250][251][252][253][254][255][256][257][258][259][260], see Table (4).…”
Section: Combining Electrochemical Methods With Conventional Capture mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the available methods, most research focus has been given to the post-combustion methods as they can be retrofitted more easily to the existing industrial units, compared to the Oxy-fuel and Pre-combustion methods [229]. Traditional post-combustion capture methods are absorption [18,19,[231][232][233][234][235][236], adsorption [13,18,[237][238][239], membrane gas separation [240][241][242][243][244][245][246], calcium looping [19,[247][248][249] and mineral carbonation [110,[250][251][252][253][254][255][256][257][258][259][260], see Table (4).…”
Section: Combining Electrochemical Methods With Conventional Capture mentioning
confidence: 99%
“…• Limited CO 2 absorbing capacity resulted from the reaction stoichiometry and dependent on the absorbent type (e.g., low capacity as 0.4 kg CO 2 /kg-MEA or higher as 1.2 kg CO 2 /kg-NH 3 [18,269]) • High absorbent regeneration (i.e., CO 2 desorption) energy • Solvent losses caused by volatility or thermal/chemical degradation, the subsequent equipment corrosion & negative environmental impacts of solvent emissions • High sensitivity to flue gas temperature, pressure and presence of impurities, such as NOx, SOx and oxygen (i.e., oxidative degradation) [270] ( Adsorption [13,18,[237][238][239] CO 2 (g) is adsorbed on solid materials and will be recovered through temperature, pressure or vacuum swing desorption…”
Section: Combining Electrochemical Methods With Conventional Capture mentioning
confidence: 99%
“…For chemical activation, KOH reacted with char to convert some carbon and oxygen from char into organic species (K 2 CO 3 ). Meanwhile, at higher temperatures (800-1100 • C), certain oxygen and K metals from KOH were released to become gas or bio-oil by-products [19,90]. It can be concluded that if the activation temperature is too high, the micropore structure will be destroyed, thus decreasing the char yield.…”
Section: Bet Surface Area and Porositymentioning
confidence: 99%
“…Adsorbents are the cornerstones for all adsorption processes, and numerous porous solid adsorbents have been developed for CO2 adsorption in post-combustion gas conditions. However, these materials suffer either from low CO2 affinity or low moisture toleration, and more importantly, are primarily used at low temperatures (under 30 °C) due to their rapid decline in capture capacity at higher temperatures [17][18][19]. N-functionalized solid adsorbents (NFSAs) are a group of adsorbents that have shown stronger CO2 affinity than bare, porous adsorbents and have better moisture tolerance.…”
Section: Introductionmentioning
confidence: 99%